Campbell essential biology with physiology : global edition - Simon, Eric J., ....-; Dickey, Jean L., ....-; Reece, Jane B., 1944-; Burton, Rebecca S., ....- (Harlow : Pearson Education Limited, 2020)
Campbell Essential Biology with Physiology helps students focus on the concepts that are most fundamental to understanding biology. Through carefully developed features, it continues to enable students to relate biology concepts to their everyday lives, understand the process of science, and appreciate the central role of evolution in biology.
Keywords: Biologie